Tourism geographies in the 'Asian Century'. Issue 4 (1st July 2021) - Sin, Harng Luh; Mostafanezhad, Mary; Cheer, Joseph M.
Abstract: From the British Century of the 1800s to the American Century of the 1900s to the contemporary Asian Century, tourism geographies are deeply entangled in broader shifts in geopolitical power (Luce, 1999; Scott, 2008; Shenkar, 2006). This paper considers what the transition into the Asian Century means for some of the most urgent issues of our time such as sustainable development, human rights, gender equality, and environmental change. We critique Anglo-Western centrism in tourism theory and call on tourism scholars to make radical shifts toward more inclusive epistemology and praxis. In the shadow of the COVID-19 pandemic, the significance of the themes addressed are more urgent than ever. The pandemic has hastened claims that the Asian century has further accelerated given the contrasting successes of many Asia-Pacific countries, especially as compared to their Euro-American counterparts (Park, 2020). As critical tourism scholars, we are faced with an unprecedented situation, even as the pandemic looks set to become globally endemic and the true extent of its fullest impacts are only beginning to emerge, with more to surface in the years ahead. That the world faces increasing turmoil is abundantly clear. Yet, amidst the disruption to the everyday, it is hope and compassion, but also political-economic restructuring that is needed to reset the tourism industry in more sustainable, equitable, and ethical directions (Cheer, 2020; Lew, Cheer, Haywood, Brouder, Salazar, 2020; Mostafanezhad, 2020). While in no uncertain terms, the pandemic has forever changed the tourism industry as we once knew it, it is our hope that we can collectively build on the momentum of the inclusive scholarship that Critical Tourism Studies-Asia Pacific is renowned for (Edelheim, 2020; Pernecky, 2020) as we pause to reflect on the possibilities and challenges of tourism in a post-pandemic Asian Century.